2020
DOI: 10.1177/0954407020965028
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of electric cars in platoon SAGE publications

Abstract: The potential aerodynamic benefits of operating full-scale electric vehicles in platoons of 2 and 3 vehicles have been investigated. Since drag reduction has a direct impact on vehicle range, power consumption was measured directly and surface pressure measurements were made to characterise the changes in pressure field that influence the power required to overcome aerodynamic drag. CFD simulations were validated against the track measurements to assess the limitations of using a practical, limited number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…These observations contradict the slip-streaming effect as it is commonly understood, however, it agrees with remarks made by other researchers on platoons of vehicles in pairs [5,7,8,13,16,23,31]. This suggests that the slip-streaming effect is not universal and is highly dependent on the chosen geometry and distance between these geometries, which may help explain the misconceptions associated with this term.…”
Section: Overall Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…These observations contradict the slip-streaming effect as it is commonly understood, however, it agrees with remarks made by other researchers on platoons of vehicles in pairs [5,7,8,13,16,23,31]. This suggests that the slip-streaming effect is not universal and is highly dependent on the chosen geometry and distance between these geometries, which may help explain the misconceptions associated with this term.…”
Section: Overall Analysissupporting
confidence: 79%
“…Velocity and pressure contours were not provided in this manuscript as the observations made were largely similar to those reported in [5,7], which explains the fundamental reasons a trailing vehicle exhibits a drag increase in certain arrangements and spacing. In addition, due to the bespoke nature of this investigation, no experimental research data was found to compare this dataset.…”
Section: Two-vehicle Platoonmentioning
confidence: 87%
See 1 more Smart Citation
“…k-turbulent energy, ε-dissipation rate, vl & vt laminar and turbulent kinematic viscosities [14][15][16].…”
Section: Energy Dissipation Equationmentioning
confidence: 99%
“…They then continued the work into CFD simulation of heavily simplified automotive body, finding that the k − model was able accurately predict the intake of pollutants. Ebrahim et al [11] used the Realizable k − model to compare CFD results of electric passenger vehicle platoons to data gathered through track testing and found that the Realizable k − was not able to predict the drag on the vehicles with great accuracy, leading to a large discrepancy between the calculated power usage of the vehicles and the actual. A notable CFD work in the study of drafting is Pagliarella [12] who performed wind tunnel testing on a variety of slant angles, determining that the vortices created from the rear of the lead Ahmed body were impinged upon by the trailing body.…”
Section: Introductionmentioning
confidence: 99%